Effect of high hydrostatic pressure treatments on physicochemical properties, microbial quality and sensory attributes of beef carpaccio - Szerman, Natalia; Barrio, Yanina Ximena; Schroeder, Belén; Martinez, Paula; Sancho, Ana Maria; Sanow, Luis Claudio; Vaudagna, Sergio Ramon (2019)
11th International Congress on Engineering and Food (ICEF11), Atenas, Grecia, 22-26 May 2011